Menganalisis Tren dan Tantangan di Dalam Teknologi Berdasarkan Penilaian Bahasa - Beby Florencia Putri; Kurniawan, Ridho Kurniawan (Journal Of Language Education and Development (JLed), 2024)
This research aims to analyze trends and challenges in technology based on language assessment for students. Technology assessment is an assessment related to media and advanced electronics such as smartphones, tablets, computers, and so on. The method that the author uses is the SLR method or Systematic Literature Review, where in the process of creating this journal, the author collects all the data that the author selects and the author enters it into this journal. The advanced technology trends that the author uses are the Quizizz and Electronic Assessment applications, both of which have many uses in helping educators assess student performance and skills. However, this is not necessarily just an advantage, but in these two technologies there are challenges that are difficult to control and students often lack self-confidence regarding the value they get from implementing the technology. So this technology has two different properties, namely that it can be useful but also has its own negative impacts.